Another Sign of Scribal Copying in the Mythological Texts in Ugaritica V - Coote, Robert В.
ersch. 1975; mistaken writing of ‛ for ṭ suggests scribe was copying a non-cuneiform alphabetic text into alphabetic cuneiform.